Short-term effects on emergency room access or hospital admissions for cardio-respiratory diseases: methodology and results after three years of functioning of a waste-to-energy incinerator in Turin (Italy). Issue 5 (4th May 2022) - Gandini, M.; Farina, E.; Demaria, M.; Lorusso, B.; Crosetto, L.; Rowinski, M.; Ivaldi, C.; Cadum, E.; Bena, A.
ABSTRACT: This study is part of the health surveillance system set up with the construction of a waste-to-energy (WTE) plant in Turin (Italy). Circulatory and respiratory diseases in emergency room (ER) accesses and first hospital admissions were considered. Main concerns of population living in the area near WTE were to know whether single and repeated peaks in emissions would correspond to adverse health effects. We tackle this issue using spatio-temporal analyses, comparing an exposed group (EXP) living near the WTE with a reference group (NOEXP). Age-standardized rates of ER accesses between EXP and NOEXP were temporally compared, testing whether there have been significantly different changes over time. We also examined the relationship between emission peaks and ER accesses in the following days. Finally, with time-series analysis, we investigated variations in ER accesses and pollutants before and after WTE start-up. No significant relationship has been found for the outcome considered.